Making sense of Bolkestein-bashing: trade liberalization under segmented labor markets - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2005)
Trade liberalization is often met with sharp opposition. Recent examples include the so-called Bolkestein directive, which allows service providers from a given EU member to temporarily work in another member country. One way to view such a reform is that it simply widens the range of goods that are tradeable. This kind of reform is analyzed in a two-country Dornbusch-Fischer-Samuelson style model, where labor cannot relocate to another sector upon a non expected increase in the range of goods that can be traded. The effect of liberalization on the terms of trade tends to favor the poorer country (the East), if (as assumed) the most sophisticated goods are tradeable before reform. Second, under ex-post liberalization, there exists a class of workers in the West who are harmed because they face competition from Eastern workers and cannot relocate to other activities. But if the East's economy is relatively small, their wage losses are not very large. Things are different, however, if there exist asymmetries in labor market institutions, such that upon reform, labor can relocate in the East but not in the West. Some workers in the West can then experience very large wage losses. Thus, rigid labor markets in the West magnify opposition to reform there.
Keywords: F16; F11; F13; 330; trade liberalization; European integration; Bolkestein directive; labor mobility; labor market institutions; comparative advantage; terms of trade; Außenhandelsliberalisierung; Arbeitsmarktsegmentierung; Internationale Arbeitsmobilität; Internationaler Dienstleistungsverkehr; Europäische Integration; EU-Staaten